Conceptualising the term Islamic in Islamic schools: the Tanzanian experience - Gunda, Janja M.; Alwi, Nor Hayati; Abd Rahman, Fadzilah; Krauss, Steven Eric; Hamzah, Azimi (Universiti Putra Malaysia Press, 2016)
Conceptualizing the term Islamic means the process of reconciling the different uses of the adjective Islamic. There have been attempts to conceptualize the role of Islam in different levels of educational institutions by documenting the applicability of its epistemology and institutional value to the development of holistic human beings. Following privatization in the early 1990s, Tanzania incorporated religious institutions, including Islamic schools, in the mainstream education system. This conceptual paper aims to reflect the use of the adjective Islamic in Islamic schools in Tanzania. The paper reflects its various classifications and suggests key questions to reconcile the incoherent use of the adjective Islamic in Islamic schools. It is hoped that the paper will further contribute to the scholarly discourse on educating students through its provision of a philosophically comprehensive Tawhidic paradigm and integrated knowledge. The literature search conducted through ERIC, ProQuest, PsycArticles and PsycINFO and Islamic electronic journals and texts provided valuable and reliable information for this paper. The results show that the adjective Islamic in Islamic schools can mean education for Muslims, education of Muslims, education about Muslims and education in the Islamic spirit. It is concluded that sustained intellectual and spiritual commitment and reflection is needed by intellectuals and parents to realize the essence of the term Islamic of Islamic schools.